Conceptualizing Patience in Islamic Literature and Positive Psychology - Ahmad Hidayat; Wina Diana Sari; Halim Purnomo; Lisfarika Napitupulu; Iredho Fani Reza (SCAD Independent, 2026)
The development of Islamic psychology in Indonesia increasingly demands integrative frameworks that bridge local cultural heritage and contemporary psychological theory. This study aimed to comparatively examine the concept of patience as articulated in Gurindam Dua Belas by Raja Ali Haji, rooted in Islamic moral values, and the framework of Sarah Schnitker within Western positive psychology. Employing a qualitative comparative design based on library research, this study analyzed classical literary texts and key psychological works using content analysis to identify convergences and divergences in conceptualizing patience. The findings revealed three core dimensions of patience—self-awareness, social interaction, and beneficial values—which correspond respectively to interpersonal patience, life hardship patience, and daily hassles patience in Schnitker’s model. While Raja Ali Haji emphasized patience as obedience to God and moral self-restraint, Schnitker highlighted human agency, emotional regulation, and adaptive coping in facing life challenges. Despite these epistemological differences, both perspectives converged in viewing patience as a multidimensional form of self-regulation essential for personal resilience and social harmony. This study contributes theoretically by integrating Islamic literary psychology with positive psychology and offers practical implications for culturally grounded counseling, character education, and mental health interventions within the Indonesian context.